Development of a seroepidemiological tool for bat-borne and shrew-borne hantaviruses and its application using samples from Zambia. - Rakiiya Sikatarii Sarii; Masahiro Kajihara; Zuoxing Wei; Sithumini M W Lokpathirage; Devinda S Muthusinghe; Akina Mori-Kajihara; Katendi Changula; Yongjin Qiu; Joseph Ndebe; Bernard M Hang'ombe; Fuka Kikuchi; Ai Hayashi; et al. (PLoS Neglected Tropical Diseases)
Background Rodent-borne orthohantaviruses are the causative agents of hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome. Apart from the classic rodent-borne hantaviruses, numerous species of hantaviruses have been identified in shrews and bats; however, their antigenicity and pathogenicity are unknown. This study focused on developing a serological method to detect antibodies against bat- and shrew-borne hantaviruses. Methodology/principal findings Five bat-borne (Brno, Dakrong, Quezon, Robina, and Xuan Song) and 6 shrew-borne (Asama, Altai, Cao Bang, Nova, Seewis, and Thottapalayam) viruses were selected based on the phylogenetic differences in their N proteins. The recombinant N (rN) proteins of these viruses were expressed as antigens in Vero E6 and 293T cell lines using the pCAGGS/MCS vector. Antisera against the Nus-tagged rN fusion proteins of these viruses (mouse anti-Brno, Dakrong, Quezon, Robina, Xuan Song, Asama, Cao Bang, and Nova, while rabbit anti-Altai, Seewis and Thottapalayam) were also generated. Antigenic cross-reactivity was examined in antisera and rN-expressing Vero E6 cells. The rN proteins of almost all the tested viruses, except for the Quezon and Robina viruses, showed independent antigenicity. For serological screening of bat samples, 5 rNs of the bat-borne viruses were expressed together in a single transfection protocol. Similarly, 6 rNs of shrew-borne viruses were expressed. Reactivities of the mixed antigen system were also examined across the singly transfected Vero cell lines to ensure that all antigens were expressed. Using these antigens, bat serum samples collected from Zambia were screened using the indirect immunofluorescence antibody test (IFAT). Selected positive samples were individually tested for the respective antigens by IFAT and western blot assays using rN-expressing 293T cell lysates. Of the 1,764 bat serum samples tested, 11.4% and 17.4% were positive for bat and shrew mixed antigens, respectively. These samples showed positive reactions to the Brno, Dakrong, Quezon, Xuan Son, Robina, Asama, Altai, Cao Bang, or Thottapalayam virus antigens. Conclusions/significance These observations suggest that the mixed-antigen screening system is useful for serological screening For Orthohantavirus infections and that bats in Zambia are likely exposed to not only bat-borne hantaviruses but also to shrew-borne hantaviruses.